Management of Principal Academic Supervision in Improving Teacher Quality - Nia Kurniawati; Faiz Karim Fatkhulloh; Fitriah Yuliasari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Philosophy and theory of educational administration cover a wide range of ideas and concepts that influence the way a school principal manages a school and improves the quality of teachers. Academic supervision management is part of that process, which involves overseeing the school's academic activities to ensure that quality standards are maintained and teachers are properly trained. Some of the philosophies that might influence the principal's approach to academic supervision management include educational philosophy which emphasizes the importance of real learning experiences, philosophy which emphasizes the role of the teacher as a facilitator in the teaching and learning process, and philosophy which emphasizes the social role of the principal in creating an inclusive learning environment and beneficial for all students. Educational administration theory can also influence the principal's approach to academic supervision management. Some theories that may be relevant include management theory which emphasizes the importance of planning, organizing and controlling in managing schools effectively, leadership theory which emphasizes the role of the principal in leading and motivating teachers and students, and organizational learning theory which emphasizes the importance of facilitating the learning process for all. school members. By understanding the philosophy and theory underlying the management of academic supervision, school principals can choose the most appropriate approach to improve teacher quality and achieve school academic goals. This study aims to determine the management of school principals' academic supervision for the process of improving the quality of teachers in schools. Principals can draw on educational administration philosophy and theory to choose the right approach to managing the process. An educational philosophy that emphasizes the importance of real learning experiences can help principals develop supervision programs that provide teachers with opportunities to be directly involved in student learning experiences. Management theory that emphasizes the importance of planning, organizing, and controlling can help principals manage the supervision process effectively. Leadership theories that emphasize the principal's role in leading and motivating teachers can help principals create a positive and supportive supervision environment. By understanding the philosophy and theory underlying the management of academic supervision, school principals can develop effective strategies to improve the quality of teachers in schools.